FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGGUNA SAP DAN DAMPAKNYA TERHADAP KINERJA INDIVIDU (STUDI PADA KANTOR DIREKSI PT PERKEBUNAN NUSANTARA X) - Meilania Berlianti Hapsari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of the study is to examine the factors affecting Enterprise Resource Planning (ERP) users’ satisfaction, particularly the System Application and Products in Data Processing (SAP) users, by adapting the success model of system information system developed by DeLone and McLean (2003) and Myers (1997). This research is administered in the Director Office of PT Perkebunan Nusantara X, Surabaya. 65 employees using SAP in their professional activities are purposively selected as samples. The primarily data are collected through questionnaire and analyzed by means of SmartPLS 2.0 tools. The results if the study shows that the service quality does not affect the SAP users’ satisfaction; on the other hand, system and information qualities positively and significantly influence their satisfaction. This study also confirms that the SAP users’ satisfaction gives positive and significant effect on the individual performance in the Director Office of PT Perkebunan Nusantara X, Surabaya.Keywords: Service quality, information quality, system quality, satisfaction of SAP user, and individual performance.